ADVANCES IN FOOD AND NUTRITION RESEARCH. - Toldra, Fidel, editor 248465 (London : Academic Press, 2019)
1. Genetic determinants of beverage consumption: Implications for nutrition and health Marilyn C. Cornelis 2. Current feeding strategies to improve pork intramuscular fat content and its nutritional quality C.M. Alfaia, P.A. Lopes, M.S. Madeira, J.M. Pestana, D. Coelho, F. Toldra and J.A.M. Prates 3. Dairy foods and positive impact on the consumer's health Silvani Verruck, Celso Fasura Balthazar, Ramon Silva Rocha, Ramon Silva, Erick Almeida Esmerino, Tatiana Colombo Pimentel, Monica Queiroz Freitas, Marcia Cristina Silva, Adriano Gomes da Cruz and Elane Schwinden Prudencio 4. Food-derived bioactive peptides and their role in ameliorating hypertension and associated cardiovascular diseases Advaita Ganguly, Kumakshi Sharma and Kaustav Majumder 5. Effects of phytochemicals against diabetes Merve Bacanli, Sevtap Aydin, Nursen Basaran and A. Ahmet Basaran 6. DMHF (2,5-dimethyl-4-hydroxy-3(2H)-furanone), a volatile food component with attractive sensory properties, brings physiological functions through inhalation K. Arihara, I. Yokoyama and M. Ohata 7. Challenges and opportunities regarding the use of alternative protein sources: Aquaculture and insects Belen Gomez, Paulo E.S. Munekata, Zhenzhou Zhu, Francisco J. Barba, Fidel Toldra, Predrag Putnik, Danijela Bursac Kovacevic and Jose M. Lorenzo 8. Mycotoxins in food and feed Jelka Pleadin, Jadranka Frece and Ksenija Markov.